Role of the Gut Microbiome in Beta Cell and Adipose Tissue Crosstalk: A Review - Martínez-Montoro, José Ignacio; Damas-Fuentes, Miguel; Fernández-García, José Carlos; Tinahones, Francisco J. (Frontiers in Endocrinology, 2022)
In the last decades, obesity has reached epidemic proportions worldwide. Obesity is a chronic disease associated with a wide range of comorbidities, including insulin resistance and type 2 diabetes mellitus (T2D), which results in significant burden of disease and major consequences on health care systems. Of note, intricate interactions, including different molecular and signaling pathways, are necessary for the establishment and progression of these two closely related conditions. Altered cell-to-cell communication among the different players implicated in this equation leads to the perpetuation of a vicious circle associated with an increased risk for the development of obesity-related complications, such as T2D, which in turn contributes to the development of cardiovascular disease. In this regard, the dialogue between the adipocyte and pancreatic beta cells has been extensively studied, although some connections are yet to be fully elucidated. In this review, we first explore the potential pathological mechanisms linking adipocyte dysfunction and pancreatic beta cell impairment/insulin resistance. In addition, we evaluate the role of emerging actors, such as the gut microbiome, in this complex crosstalk.